Cultivating national identity with traditional culture: China's experiences and paradoxes. Issue 4 (4th July 2018) - Xu, Shuqin
ABSTRACT: Constructing national identity with collective memory based on traditional culture has long been a policy and research concern. China's recent revival of its traditional culture, previously denounced by the Communist Party of China (CPC), has caused diverse academic concerns. Yet few studies have addressed how the CPC-led state interacts with domestic actors in cultivating students' national identity with a previously denounced culture, and what paradoxes lie therein. Documentary review shows that in the process, the state is concerned about creating a consensus around providing traditional Chinese culture (TCC) education, and about maintaining its defining role in designing the project, especially when interacting with diverse actors who had different interests in TCC education.